Supply and Value Chain Models in Cattle Marketing and Its Derivative Products in East Nusa Tenggara Province - Lole, Ulrikus Romsen; Keban, Arnoldus; Sogen, Johanes G; Mulyantini, Ni Gusti Ayu (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2021)
In general, the determination of the price of cattle is based on the condition of the cattle's body. This will result in an unsatisfactory transfer of revenue value for farmers, because the bargaining position is still weak. In addition, transactions in the marketing chain of beef products and their by-products have not yet been solidly established, so the obligations and rights of some parties are not guaranteed. The objective was to analyze the role of stakeholders in each supply chain and distribution of value chains as revenue in the marketing transactions of cattle, beef, and derivative products. The study was conducted in West Timor, which has 85.0% of the cattle population in NTT. Four sample districts (Kupang, TTS, TTU and Belu) in 8 sample sub-districts or 16 sample villages were included in the study. Respondents in marketing activities consisted of farmers, village traders, sub-district/district traders, slaughter traders, inter-island traders, by-product/waste traders, as well as beef, cowhide, bone, and fat/blood processing industries. Data collection were conducted by a questionnaire-based interview. The data were analyzed descriptively-quantitatively with a supply chain analysis model. It canbe concluded that (1) Market supply chains include cattle traders (farmers, village traders, sub-district traders, inter-island traders and slaughtering traders), as well as beef traders (fresh beef retailers, frozen beef exporting traders, and processed beef products traders); (2) The ideal model of the value chain in the form of revenue share from marketing of cattle, beef, processed beef products, by-products, and cattle waste has not been fully established in NTT; (3) The ideal model includes five marketing blocks (cattle block, beef block, processed beef block, by-product block, and waste block).